Kuasa Jibril dari Sufisme Perenial Salamullah hingga Salamullah Eden - Achmad Yasin (PT. Hasba Edukasi Mandiri, 2026)
This article examines Jamaah Salamullah, later known as the Eden Community, as a religious–spiritual phenomenon that occupies a hybrid position between traditional Sufi orders and contemporary spiritual movements. The movement is conceptualized as perennial–messianic Sufism, a form of spirituality that combines perennialism—the idea that all religions ultimately converge upon a single Divine Reality—with the doctrine of the regulation of the soul, which incorporates elements of reincarnation and ontological evolution. This synthesis provides a theological foundation for the community’s messianic claims while positioning mystical experience as the primary source of religious authority. From a sociological perspective, the transformative vision of Salamullah/Eden strongly appeals to segments of the urban middle class seeking spiritual solutions to the crisis of meaning brought about by modernity. In this sense, the Eden Community can be understood as a local New Age–type movement that forges strong member commitment through intensive rituals, shared sacred experiences, and the construction of a distinct collective identity within the landscape of urban religiosity in Indonesia.